Karakteristik Dan Klasifikasi Anak Bekebutuhan Khusus - Cici Fitri Yandes; Ika Setiowati; Sulaini Sulaini; Yupita Sri Rizky; Rian Saputra; Opi Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to explore the characteristics of children with special needs (ABK) in the context of physical, social and cognitive development. Research methods involve direct observation, interviews with parents and educators, and analysis of related literature. The research results show large variations in the levels of limitations and potential of children with special needs. Challenges in social interaction, language development and motor skills are the main focus. These findings emphasize the importance of an individualized approach and tailored support to facilitate optimal growth of children with special needs. The implications of education and intervention are discussed as a basis for efforts to improve the quality of life and social inclusion for children with special needs.